2020
DOI: 10.21276/aanat.2020.6.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Morphological Variations in Lumbricals of Hand

Abstract: Introduction: The lumbrical muscles are unique in their functions in being only intrinsic muscles which bridges between the palmar and dorsal surface. This unique property endows them in performing fast, alternating movements and fine tuning digit motion. The aim of this study was to evaluate the anatomical variations in the morphology and architecture of lumbricals and to discuss its clinical implications. Subjects and Methods: This study was conducted on 74 disarticulated upper limbs during routine dissectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…5 Afroze et al conducted a case study on lumbricals where they found hypertrophy of 1st lumbricals in one cadaver out of total 74 dissected cadavers. 6 They also concluded variation in 2nd lumbrical in 2 cadavers. And split insertion in 3rd and 4th lumbricals.…”
Section: Discussionmentioning
confidence: 95%
“…5 Afroze et al conducted a case study on lumbricals where they found hypertrophy of 1st lumbricals in one cadaver out of total 74 dissected cadavers. 6 They also concluded variation in 2nd lumbrical in 2 cadavers. And split insertion in 3rd and 4th lumbricals.…”
Section: Discussionmentioning
confidence: 95%